PENGGUNAAN VIDEO ANIMASI DALAM MENINGKATKAN PEMAHAMAN MATERI DAUR HIDUP HEWAN PADA SISWA CEREBRAL PALSY KELAS VIII SMPLB NEGERI 1 MAKASSAR - Nasir, Khaerunnisa; Faizal; Tatiana Meidina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem examined in this research is based on motoric limitations and the difficulty students with cerebral palsy have in maintaining concentration, resulting in a low ability to understand the animal life cycle in science. The purpose of this study was to determine the animal life cycle comprehension skills of students with cerebral palsy through the use of animated videos. The data collection technique used was a pretest and posttest. The subject in this study was a 15-year-old eighth-grade cerebral palsy student, identified as AF. This study used a quantitative approach with a descriptive research style. Data analysis was conducted by comparing test results before and after treatment and describing the improvements that occurred. The results of this study were: (1) the comprehension skills of students with cerebral palsy before the animated video were in the poor category with a score of thirty; (2) the comprehension skills of students with cerebral palsy after the animated video were in the very good category with a score of ninety; (3) there was an increase in students' understanding of the animal life cycle after the animated video, from the poor category to the very good category. Thus, using animated videos of the frog's life cycle can help improve students' understanding of the frog's life cycle.